Combined Effect of Blood Pressure and Total Cholesterol Levels on Long-Term Risks of Subtypes of Cardiovascular Death: Evidence for Cardiovascular Prevention From Observational Cohorts in Japan. Issue 3 (March 2015) - Satoh, Michihiro; Ohkubo, Takayoshi; Asayama, Kei; Murakami, Yoshitaka; Sakurai, Masaru; Nakagawa, Hideaki; Iso, Hiroyasu; Okayama, Akira; Miura, Katsuyuki; Imai, Yutaka; Ueshima, Hirotsugu; Okamura, Tomonori
Abstract : No large-scale, longitudinal studies have examined the combined effects of blood pressure (BP) and total cholesterol levels on long-term risks for subtypes of cardiovascular death in an Asian population. To investigate these relationships, a meta-analysis of individual participant data, which included 73 916 Japanese subjects (age, 57.7 years; men, 41.1%) from 11 cohorts, was conducted. During a mean follow-up of 15.0 years, deaths from coronary heart disease, ischemic stroke, and intraparenchymal hemorrhage occurred in 770, 724, and 345 cases, respectively. Cohort-stratified Cox proportional hazard models were used. After stratifying the participants by 4 systolic BP ×4 total cholesterol categories, the group with systolic BP ≥160 mm Hg with total cholesterol ≥5.7 mmol/L had the greatest risk for coronary heart disease death (adjusted hazard ratio, 4.39; P <0.0001 versus group with systolic BP <120 mm Hg and total cholesterol <4.7 mmol/L). The adjusted hazard ratios of systolic BP (per 20 mm Hg) increased with increases in total cholesterol categories (hazard ratio, 1.52; P <0.0001 in group with total cholesterol ≥5.7 mmol/L). Similarly, the adjusted hazard ratios of total cholesterol increased with increases in systolic BP categories ( P for interaction ⩽0.04). Systolic BP was positively associated with ischemic stroke and intraparenchymal hemorrhage death, and total cholesterol was inversely associated with intraparenchymal hemorrhage, but no significant interactions between BP and total cholesterol were observed for stroke. High BP and high total cholesterol can synergistically increase the risk for coronary heart disease death but not for stroke in the Asian population. Abstract : Supplemental Digital Content is available in the text.